2018
DOI: 10.1177/0300060518793036
|View full text |Cite
|
Sign up to set email alerts
|

Open reduction and internal fixation of intra-articular distal radius fractures under wide-awake local anesthesia with no tourniquet

Abstract: ObjectiveThe use of wide-awake local anesthesia with no tourniquet (WALANT) is becoming an excellent alternative for elective hand surgeries and hand surgeries involving minor trauma. Although the use of WALANT for some soft tissue surgeries has become the state of the art, data regarding bony procedures, such as fracture management, under WALANT are limited. This study was performed to assess the WALANT technique for open reduction and internal fixation of distal radius fractures.MethodsFive patients with dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 22 publications
(39 reference statements)
0
20
0
1
Order By: Relevance
“…The use of WALANT in plating distal radius fractures has been reported with good results (Ahmad et al., 2018; Huang et al., 2018; Orbach et al., 2018). Huang et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of WALANT in plating distal radius fractures has been reported with good results (Ahmad et al., 2018; Huang et al., 2018; Orbach et al., 2018). Huang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Its use in distal radius fractures would make it possible to perform intraoperative motor testing, to evaluate the stability of the fixation under active muscle contractions, and to assess the potential impingement of the flexor pollicis longus (FPL) tendon on the plate. Feasibility of this technique in distal radius fractures has been briefly evaluated (Ahmad et al., 2018; Huang et al., 2018; Orbach et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The WALANT technique was only last year reported as an anaesthesia option for surgery of distal radius fractures. 12 - 14 The technique and one case were first described by Ahmad et al, 12 and Orbach et al 13 subsequently described successfully operating on five cases. Orbach et al 13 concluded that the WALANT technique offers a simple and safe alternative to traditional anaesthetic techniques for surgery on distal radius fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Jedoch werden zunehmend auch ausgedehntere elektive Eingriffe in WALANT-Technik beschrieben, wie z. B.: ▪ Arthroskopien [25], ▪ Plattenosteosynthesen bei Radiusfrakturen [17], ▪ Implantationen trapeziometakarpaler Prothesen bei Rhizarthrosen [26], ▪ Resektionsarthroplastiken. Hinsichtlich des klinischen Outcomes konnte bisher keine Überlegenheit der WALANT-Technik gegenüber herkömmlicher Anästhesie für die meisten Indikationen bewiesen werden [3].…”
Section: Indikationen Für Walant-verfahrenunclassified